Power efficiency of the converter of the ultisystem electric locomotive converter in the alternate current mode - Муха, Андрій Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The Presented results of the determination coefficient of efficiency unified converter of much system electric locomotive, when run under contact network of alternating current